Dynamic modeling and collocation‐based model reduction of cryogenic air separation units. Issue 5 (26th January 2016) - Cao, Yanan; Swartz, Christopher L. E.; Flores‐Cerrillo, Jesus; Ma, Jingran
Abstract : High purity distillation columns and multi‐stream heat exchangers (MSHXs) are critical units in cryogenic air separation plants. This article focuses on modeling approaches for the primary section of a super‐staged argon plant. A full‐order stage‐wise model for distillation columns in air separation units (ASUs) that considers key process phenomena is presented, followed by a reduced‐order model using a collocation approach. The extent of model reduction that can be achieved without losing significant prediction accuracy is demonstrated. A novel moving boundary model is proposed to handle MSHXs with phase change. Simulation results demonstrate the capability of the proposed model for tracking the phase change occurrence along the length of the heat exchanger. Dynamic simulation studies of the integrated plant show that the thermal integration between the feed and product streams captured in the primary heat exchanger is critical to accurately capture the behavior of ASUs. © 2016 American Institute of Chemical Engineers AIChE J, 62: 1602–1615, 2016